2020
DOI: 10.3345/kjp.2019.01060
|View full text |Cite
|
Sign up to set email alerts
|

Importance of pulmonary valve morphology for pulmonary valve preservation in tetralogy of Fallot surgery: comparison of the echocardiographic parameters

Abstract: Background: The decision to use transannular patching (TAP) during tetralogy of Fallot (TOF) repair depends on the pulmonary valve annulus size; the <i>z</i> score of the pulmonary annulus is the most commonly used predictor. However, definitive results are not obtained with <i>z</i> scores as different <i>z</i> score data sets are used for different parameters.Purpose: This study aimed to identify the echocardiographic and other key factors that warranted a change in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
(28 reference statements)
2
6
0
Order By: Relevance
“…Pulmonary valve bicuspid malformation is one reason why predictive models fail to predict the possible avoidance of TAP. This is consistent with the results reported by Choi et al 18 Although various echocardiographic parameters can be used as indicators to predict surgical approach in patients with TOF, PV morphology and tissue characteristics should also be considered.…”
Section: Pearson's Correlation and Linear Regression Analysissupporting
confidence: 92%
“…Pulmonary valve bicuspid malformation is one reason why predictive models fail to predict the possible avoidance of TAP. This is consistent with the results reported by Choi et al 18 Although various echocardiographic parameters can be used as indicators to predict surgical approach in patients with TOF, PV morphology and tissue characteristics should also be considered.…”
Section: Pearson's Correlation and Linear Regression Analysissupporting
confidence: 92%
“…The size of the pulmonary annulus, the morphology of the leaflets, and the position of the commissures are known to influence surgical outcome. 12 In addition, we were unable to verify satisfactory growth of the pulmonary valve annulus during follow up. Valve function and functional status of the right ventricle were evaluated using echocardiograms which were performed by several different cardiologists.…”
Section: Limitationsmentioning
confidence: 87%
“…Kasturi et al suggested the use of "pulmonary annulus index," calculated indirectly by using the pulmonary and aortic annulus diameters and which expresses the proportion of observed and expected pulmonary annulus diameters along with the pulmonary annulus Z-scores (15) . Choi et al stated that the ratio of pulmonary-to aortic annulus diameter and descending aorta diameter can be used for this purpose (16) . However, further studies are needed to include these new recommendations in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…In many centers, absolute value of the right ventricular pressure is measured intraoperatively, and the ratio of the right ventricular pressure to the left ventricular pressure is calculated, and the course of the operation is decided on the basis of these measurements. If the right ventricle-pulmonary artery gradient is above 40 mmHg or the right-left ventricle peak pressure ratio is above 0.8, it is recommended to switch to TAP technique, although the initial operation plan was PVSS (16) . In the study by Stewart et al, 6 of 88 patients (6.8%) who had a PVSS plan had to be switched to TAP procedure on the basis of intraoperative pressure measurements, and also 33% of patients with a right-left ventricular pressure ratio of more than 0.7% needed reoperation in follow-up.…”
Section: Discussionmentioning
confidence: 99%